Parental psychological control and depressive symptomatology in Chinese junior middle school students: a moderated mediation model - Hailun Liu; Lili Fu; Xianqi Liang; Junhua Zhang; Li Zhang; Youhua Zhai; Jiayi Zhao (BMC Psychology)
Abstract Background This study examines the mechanisms linking parental psychological control and depressive symptomatology among Chinese junior middle school students, focusing on the mediating role of psychological resilience and the moderating role of school climate. Method A questionnaire survey was conducted among 1991 middle school students using a depressive symptomatology scale, the psychological control sub-questionnaire, the Chinese version of the Connor-Davidson Resilience Scale, and the Perceived School Climate Scale. Data analysis included descriptive statistics, correlation analysis, and tests of the moderated mediation model. Results (1) parental psychological control positively predicts depressive symptomatology (β = 0.34, p < 0.001), with psychological resilience mediating this relationship (β = 0.02, 95% Bootstrap CI= [0.01, 0.04]); (2) in the mediation model, school climate moderates the first and second half pathways (β parental psychological control× school climate = -0.03, 95% Bootstrap CI= [-0.07, -0.00]; β psychological resilience × school climate = -0.08, 95% Bootstrap CI= [-0.11, -0.05]) and the mediating effect. Specifically, under a high-level school climate, the effect of parental psychological control on psychological resilience, and the effect of psychological resilience on depressive symptomatology were significantly stronger than those in a low-level school climate. The indirect effect of psychological resilience was also stronger in a high-level than a low-level school climate (Contrast high minus low level = 0.03, 95% CI [0.01, 0.05]. Psychological resilience could not moderate the psychological control–depressive symptomatology relationship. Conclusion Parental psychological control indirectly affects depressive symptomatology through psychological resilience, with school climate moderating the mediating effect. The findings show how family and school environments, along with individual traits, collectively influence adolescents’ depressive symptomatology. The study has the following application implications. Interventions such as the resilience-building program and the mindfulness program could improve parents’ educational styles and students’ psychological resilience respectively. Educators can strengthen school climate through learning guidance and game activities and so on. Courses such as teacher training should incorporate methods of family-school collaboration. Further longitudinal studies could explore the development of the relationships between the main variables. Objective measurements could also be incorporated for more accurate measurement.